32 Factorial Design Screened Abelmoschus esculentus Fruit Mucilage abetted Floating Microspheres of Clarithromycin for Exterminating Helicobacter pylori (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The study aims to investigate the floating possessions of Abelmoschus esculentus fruit mucilage by incorporating it into floating microspheres with Clarithromycin. Nine interpretations of floating microspheres were made with sodium alginate (SA) and varying proportions of A. esculentus fruit mucilage (AEFM). A central composite design with design expert software to check the impact of independent variables (AEFM and SA levels) on entrapment efficacy and floating time (FT). As part of congeniality studies, the microspheres were scrutinized for clarithromycin (CMN) content and its release. The research discovered that CMN entrapment increased with an increase in AEFM levels in the formulations and that the FT was greater in formulations with higher AEFM levels. In formulations containing higher levels of AEFM, the drug release is slightly reduced. The study revealed that Clarithromycin is capable of good stomach-specific drug delivery by formulating it with SA as floating microspheres and the assets were enhanced by AEFM.